Simón Rodríguez and José Martí: Initial Features of Latin American Critical Pedagogy - López, Diana (2011)
The reflection is shown below, presents some considerations about the main educational ideas in the nineteenth century built by American thinkers and their relationship with the spirit of later American educational streams that flow into the construction of critical pedagogy, understanding the contextual distance have given origin, showing the linkage of a regional-original thought that begins with independence and is enriching, deepening posterity. Some of the questions that cause this writing, the varied and valuable guide research efforts in the field of education and pedagogy are: Why can consider the thought of José Martí and Simón Rodríguez as the beginning of what today is conceived as critical Pedagogies?, why it can be said that there, in thinking of these early American underlie critical pedagogies? An analysis of what are the foundations of critical pedagogies and those similarities exist with the theory advanced by Simón Rodríguez and José Martí.